Entrepreneurs' Perceptions of the State Implication in the Business Environment Modelling in Romania - Ovidiu NICOLESCU; Ciprian NICOLESCU (Transylvanian Review of Administrative Sciences, 2013)
One of the main economic purposes of state administration in every country is to ensure an enabling business environment. The study has two main objectives: first, to reveal and analyze the perceptions of Romanian SMEs – 99.9% of economic companies – regarding the quality of business environment, its main opportunities and difficulties; second, to evaluate the capacity of the Romanian government to face economic crisis and its consequences. The analysis is based on the interviews of 1723 SMEs entrepreneurs and managers in 2011. We have identified a predominantly unfavorable Romanian business environment and a low capacity to face the complex elements associated with economic crisis. Conclusions are grouped at three levels of state administration – national, local and sectorial – and followed by a set of recommendations regarding the improvement of business environment.